2020
DOI: 10.3389/fmed.2020.00459
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Clinical Characteristics, and Sex-Specific Risk of Mortality: Systematic Review and Meta-Analysis

Abstract: Background: The rapidly evolving coronavirus disease 2019 (COVID-19), was declared a pandemic by the World Health Organization on March 11, 2020. It was first detected in the Wuhan city of China and has spread globally resulting in a substantial health and economic crisis in many countries. Observational studies have partially identified different aspects of this disease. There have been no published systematic reviews that combine clinical, laboratory, epidemiologic, and mortality findings. Also, the effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 66 publications
8
77
2
1
Order By: Relevance
“…Cox regression was performed to determine risk factors associated with in-hospital mortality. Clinically relevant factors were found based on our and other studies and added into the models [18][19][20][21] . We used the Charlson comorbidity index because we expected a low number of outcomes for each outcome variable and were able to include only a limited number of potential confounders from the comorbidities in the model (CCI) 22 .…”
Section: Statistical Analysis Categorical Variables Were Presented Amentioning
confidence: 99%
“…Cox regression was performed to determine risk factors associated with in-hospital mortality. Clinically relevant factors were found based on our and other studies and added into the models [18][19][20][21] . We used the Charlson comorbidity index because we expected a low number of outcomes for each outcome variable and were able to include only a limited number of potential confounders from the comorbidities in the model (CCI) 22 .…”
Section: Statistical Analysis Categorical Variables Were Presented Amentioning
confidence: 99%
“…As of December 8, 2020, WHO declared a death ratio of [9]. In a meta-analysis by Nasiri et al, the mortality rate was reported as 6.6% [10]. As we included the patients with SARI symptoms and indication for hospitalization, our results might not be not comparable with previous reports.…”
Section: Discussionmentioning
confidence: 75%
“…Bilinski and Emanuel reported 60.3 COVID-19 deaths per 100.000 for the US, 86.8 for Belgium, 65.0 for Spain, 62.6 for the UK, 59.1 for Italy, 57.4 for Sweden, 46.6 for France, and 36.2 for the Netherlands [ 9 ]. In a meta-analysis by Nasiri et al, the mortality rate was reported as 6.6% [ 10 ]. As we included the patients with SARI symptoms and indication for hospitalization, our results might not be not comparable with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While earlier studies showed that men were at higher risk of mortality after contracting COVID-19 than women, [3][4][5][6] older women and minority women are also at increased risk of mortality. [7][8][9][10] In addition to mortality, COVID-19 patients are at elevated risk of cardiovascular complications. 11,12 Furthermore, preexisting cardiovascular disease and chronic disease, such as diabetes and COPD, 13,14 have been linked to worse prognosis in COVID-19.…”
Section: Introductionmentioning
confidence: 99%